Anodic self-assembly method for synthesizing hierarchical FeS/FeOx hollow nanospheres - Bian, Haidong; Li, Zebiao; Pan, Jie; Lyu, Fucong; Xiao, Xufen; Tang, Jiaoning; Schmuki, Patrik; Liu, Chen; Lu, Jian; Li, Yang Yang (Journal of Power Sources, 2020)
Hollow nanostructured materials are attractive in material science for both fundamental research and practical applications. In this study, anodization demonstrates its convenience and effectiveness for constructing elaborate hollow nanospheres, based on an interesting synthetic mechanism involving bubble-assisted anodic self-assembly. The thus fabricated hierarchical FeS/FeOx hollow nanospheres are directly grown on the Fe substrate, providing a novel type of binder-free anode for high-performance batteries. For instance, when applied in sodium ion batteries, the air-annealed anode delivers high capacity and stability, retaining 464.8 mA h g−1 after 100 cycles at 100 mA g−1.
CRIS-Team Scopus Importer:2020-12-11
Keywords: Binder-free; Hollow nanospheres; Na-ion batteries; One-step anodization; Synthetic mechanism